Cultivating a culture of nonviolence in early childhood development centers and schools - Taukeni, Simon George, 1973- (Advances in early childhood and K-12 education (AECKE) book series., 2019)
"This book expands on multicultural nonviolent teaching techniques in early childhood development centers, schools, institutions of high learning and centers of teacher development and training to understand nonviolence concepts, its techniques, and its application to achieve desired conducive environment outcomes"- Resumé vydavatel